Cord blood albumin as predictor of neonatal hyperbilirubinemia - V., Chandan M.; K., Praveen B. (International Journal of Contemporary Pediatrics, 2020)
Background: Measuring the Cord blood Albumin level and predicting neonatal hyperbilirubinemia. Methods: Prospective study was performed on 160 healthy term neonates. Relevant maternal history was collected. Cord blood was collected from the healthy term neonates at birth and cord serum albumin measured. Neonate was assessed for jaundice every day using transcutaneous bilirubinometer. Total Serum Bilirubin (TSB) was assessed if the Transcutaneous Bilirubin (TCB) values were found high and treated according to NICU protocol. Results: Study cohort was grouped as Group A, Group B and Group C based on Cord Serum Albumin (CSA) level ≤3.3 g/dl, 3.3-3.8 g/dl and ≥3.8 g/d respectively. Statistical analysis was done for correlation of CSA with Neonatal Hyperbilirubinemia (NH). It showed that cord serum albumin level ≤3.8 g/dl is critical, as it was seen in 9.1% of neonates who developed neonatal hyperbilirubinemia (p value-0.032). Conclusions: There is a correlation between cord serum albumin level and neonatal hyperbilirubinemia. Cord serum albumin level of ≤3.8 g/dl is a risk indicator in predicting the development of neonatal hyperbilirubinemia.